Two-Hour Postprandial Lipoprotein Particle Concentration Differs Between Lean and Obese Individuals - Parvaresh Rizi, Ehsan; Baig, Sonia; Loh, Tze Ping; Toh, Sue-Anne; Khoo, Chin Meng; Tai, E. Shyong (Frontiers in Physiology, 2019)
The concentrations of lipoprotein particles [high-density lipoproteins (HDLs), low-density lipoproteins (LDLs), very-low-density lipoproteins (VLDLs), and chylomicrons] are associated with the risk of cardiovascular diseases. Most studies have examined these associations in the fasting state. Previous studies have shown lipoprotein particle concentration change following meal, and these changes are different in individuals with obesity. In this study, we aimed to assess whether various meal compositions lead to adverse short-term (2-h) postprandial lipoproteinemia in obese insulin resistant (obese-IR) subjects as compared to lean insulin sensitive (lean-IS) subjects. In a randomized crossover trial, nine lean-IS and nine obese-IR Chinese men aged 22–35 years were challenged with isoenergetic and isovolumic meals rich in protein (HP), fat (HF), or carbohydrate (HC). Plasma samples were collected after a 10-h fast, as well as 1-h and 2-h post-meal and analyzed using nuclear magnetic resonance. Plasma concentration of large VLDLs and chylomicron particles was higher and increased more after all meals in obese-IR compared to lean-IS subjects. The HP meal decreased small LDL particle concentration in obese-IR subjects, and increased small HDL particle concentration in all subjects. The HF meal led to a decrease in small HDL concentration in all subjects. In conclusion, obese-IR subjects revealed a detrimental response to meal challenges even as early as 2-h after meal intake.